2022
DOI: 10.1101/2022.09.16.508001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brassinosteroid gene regulatory networks at cellular resolution

Abstract: Brassinosteroids (BRs) are plant steroid hormones that regulate diverse processes such as cell division and cell elongation. BRs control thousands of genes through gene regulatory networks (GRNs) that vary in space and time. We used time series single-cell RNA-sequencing to identify BR-responsive gene expression specific to different cell types and developmental stages of the Arabidopsis root, uncovering the elongating cortex as a site where BRs trigger a shift from proliferation to elongation associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 187 publications
(513 reference statements)
0
22
0
Order By: Relevance
“…This analysis illustrates any dimorphism resulting from the condition (particular TF combination) and may help to determine if specific cell types are targeted by the mechanism. UMAP has already been used for gene expression analysis according to cell types (Nolan et al, 2023).…”
Section: Cartlu-plot To Visualize the Best Tfcimentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis illustrates any dimorphism resulting from the condition (particular TF combination) and may help to determine if specific cell types are targeted by the mechanism. UMAP has already been used for gene expression analysis according to cell types (Nolan et al, 2023).…”
Section: Cartlu-plot To Visualize the Best Tfcimentioning
confidence: 99%
“…scRNA-seq are on the path to change transcriptomic studies forever as they provide an unprecedented accurate measure of gene expression in every cell of an organism and a wealth of data (Shahan et al, 2022;Nolan et al, 2023). Among the first scRNA-seq studies, we count those applied to Arabidopsis root being a very good model for such studies thanks to its concentric well defined cell layers that recapitulate a very well defined developmental program (Shahan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the input of abiotic and biotic cues that fine-tune growth and development according to the environment of the developing root has seen a rise in interest. Additionally, omics approaches, and validation of these techniques are becoming more potent, starting with the global transcriptomic that lead to the first Arabidopsis root atlas expression map (Birnbaum et al, 2003; Nawy et al, 2005; Brady et al, 2007; Li et al, 2016) and currently the single-cell technologies in Arabidopsis and other species (Efroni et al, 2016; Guillotin et al, 2023; Nolan et al, 2023; Shahan et al, 2021; Zhang et al, 2019).…”
Section: Perspectivesmentioning
confidence: 99%
“…A time‐series scRNA‐seq analysis of brassinosteroid (BR) treatment response in Arabidopsis roots revealed that brassinosteroids trigger a shift from proliferation to elongation in cortex cells by inducing cell wall‐related genes, and identified two BR‐induced TFs specifically affecting the cortex trajectories. They functionally confirmed the role of these TFs in mediating BR‐induced cell elongation via the upregulation of cell wall‐related genes (Nolan et al ., 2023). In another study profiling the Arabidopsis root after cytokinin (CK) treatment, the authors demonstrated that an increase in CK levels is counteracted by the upregulation of CYTOKININ OXIDASE 3 in procambium cells via the activation of the mobile TF SHORTROOT, to ensure well‐balanced CK levels (Yang et al ., 2021).…”
Section: Precise Phenotyping Of Plantsmentioning
confidence: 99%